The FGFR inhibitor Rogaratinib reduces microglia reactivity and synaptic loss in TBI - Rehman, Rida; Froehlich, Albrecht; olde Heuvel, Florian; Elsayed, Lobna; Boeckers, Tobias; Huber-Lang, Markus; Morganti-Kossmann, Cristina; Roselli, Francesco (Frontiers in Immunology, 2024)
BackgroundTraumatic brain injury (TBI) induces an acute reactive state of microglia, which contribute to secondary injury processes through phagocytic activity and release of cytokines. Several receptor tyrosine kinases (RTK) are activated in microglia upon TBI, and their blockade may reduce the acute inflammation and decrease the secondary loss of neurons; thus, RTKs are potential therapeutic targets. We have previously demonstrated that several members of the Fibroblast Growth Factor Receptor (FGFR) family are transiently phosporylated upon TBI; the availability for drug repurposing of FGFR inhibitors makes worthwhile the elucidation of the role of FGFR in the acute phases of the response to TBI and the effect of FGFR inhibition.MethodsA closed, blunt, weight-drop mild TBI protocol was employed. The pan-FGFR inhibitor Rogaratinib was administered to mice 30min after the TBI and daily up to 7 days post injury. Phosphor-RTK Arrays and proteomic antibody arrays were used to determine target engagement and large-scale impact of the FGFR inhibitor. pFGFR1 and pFGFR3 immunostaining were employed for validation. As outcome parameters of the TBI injury immunostainings for NeuN, VGLUT1, VGAT at 7dpi were considered.ResultsInhibition of FGFR during TBI restricted phosphorylation of FGFR1, FGFR3, FGFR4 and ErbB4. Phosphorylation of FGFR1 and FGFR3 during TBI was traced back to Iba1+ microglia. Rogaratinib substantially dowregulated the proteomic signature of the neuroimmunological response to trauma, including the expression of CD40L, CXCR3, CCL4, CCR4, ILR6, MMP3 and OPG. Prolonged Rogaratinib treatment reduced neuronal loss upon TBI and prevented the loss of excitatory (vGLUT+) synapses.ConclusionThe FGFR family is involved in the early induction of reactive microglia in TBI. FGFR inhibition selectively prevented FGFR phosphorylation in the microglia, dampened the overall neuroimmunological response and enhanced the preservation of neuronal and synaptic integrity. Thus, FGFR inhibitors may be relevant targets for drug repurposing aimed at modulating microglial reactivity in TBI.